Elements for economic evaluation on online Hemodiafiltration (ol-HDF) versus standard Haemodialysis to treat patients with End-Stage Renal Disease (ESRD) (Italian Journal of Public Health, 2012)
In a recent survey among more than 6 000 nephrology professionals, almost half were in favour of the use of high-flux HD and HDF as their best option for extracorporeal dialysis therapy. An analysis of clinical literature suggests that on-line HDF provides an increase in years of life gained, a reduction of adverse events, reduced hospitalizations, a reduced use of drugs and improved organizational efficiency. All the following elements have...